Role Vitalized by Clinical Pharmacists in Drug Information Services: A Cross-Sectional Analysis in a Tertiary Care Hospital - Paul, Eldho Mathew; Joy, Sneha; Abraham, Emi Rose; Varghese, Dinu; John, Susan; John, Jibin; James, Janet Maria (Indian Journal of Pharmacy Practice)
Objectives: To analyze the pivotal role of clinical pharmacists illustrated via their expertise in drug information services and to justify the crucial need to establish structured drug information centers for upgrading quality of patient care. Materials and Methods: A comprehensive cross-sectional analysis conducted at the Department of Clinical Pharmacology and ADR monitoring center of a tertiary care hospital, from July 2019 to June 2024, elucidated the query patterns and assessed the impact of clinical pharmacists on therapeutic decision making. Results: The study findings underscored a profound correlation between clinical pharmacist’s interventions and the growing number of information utilizers. Prompt and evidence-based responses were facilitated which delivered informed clinical judgments and aided in mitigating medication errors. Notably, the inquiry revealed a preponderance of queries pertaining to pharmacotherapy and pharmaceuticals, with physicians and nurses being the primary beneficiaries of this service. Conclusion: This research highlights the indispensable contribution of clinical pharmacists to drug information services, emphasizing the imperative need for structured drug information center at hospital to promote judicious prescribing practice, ensuring medication safety, and optimize patient well-being by reaching out to the general public.
Keywords: Clinical pharmacists; Drug information services; Rational prescribing; Evidence based practice; Clinical decision making; Health-care quality